ANALISIS FRAMING BERITA KERUSUHAN DAN DISKRIMINASI DI PAPUA PADA MEDIA DARING TIRTO.ID: ANALISIS FRAMING BERITA KERUSUHAN DAN DISKRIMINASI DI PAPUA PADA MEDIA DARING TIRTO.ID - Yusuf, Maulana; Muh. Akbar; Alem Febri Sonni (KAGANGA KOMUNIKA: Journal of Communication Science, 2024)
The purpose of this study is to examine the framing of news about riots and ethnic discrimination in Papua on online media Tirto.id. This research uses a qualitative method with Robert Entman's media framing theory which formulates framing from four framing models, namely, Define Problems, where this relates to how the issue can occur. Second, Diagnose Causes, which is related to what causes the issue to emerge. Third, Make a Moral Judgment, which is related to the moral values contained in the issue. Fourth, Treatment Recommendation, which is related to problem-solving or recommendations on the issue. The results showed (Define Problem) defining the problem of riots and discrimination reported by Tirto.id related to riots in Papua as a humanitarian problem. As previously known, the protests that caused riots in Papua were a form of anger from the Papuan people over the events that occurred in Surabaya. (Diagnose causes) reported by Tirto.id is the alleged acts of racism, discrimination, and intimidation committed by unscrupulous mass organizations and unscrupulous officers against Papuan students in Surabaya. In addition, acts of racism and discrimination committed by unscrupulous mass organizations and unscrupulous officials against Papuan students in Surabaya and Malang are behaviors that should be resolved and stopped. Tirto.id's moral judgment (Make moral judgment) is that the riots and discrimination in Papua should be resolved by the government with an emotional approach. (Treatment Recommendation) Tirto.id emphasizes that the government must learn from history regarding solving problems in Papua. Tirto.id emphasizes that solving the problem of riots in Papua should be done with a Social, Political, and Cultural approach. Tirto.id emphasizes that the government must learn from history regarding solving problems in Papua.  Keywords: Framing Analysis, Riots and Discrimination, Papua, Tirto.id.